FC 063DAPAGLIFLOZIN DECREASES ALBUMINURIA IN PATIENTS WITH CHRONIC KIDNEY DISEASE WITH AND WITHOUT TYPE 2 DIABETES: INSIGHTS FROM THE DAPA-CKD TRIAL. (29th May 2021) - Jong, Niels; Chertow, Glenn; Hou, Fan Fan; McMurray, John; Correa-Rotter, Ricardo; Rossing, Peter; Sjöström, David; Stefansson, Bergur; Toto, Robert; Langkilde, Anna Maria; Wheeler, David C; Lambers Heerspink, Hiddo
Abstract: Background and Aims: Reductions in albuminuria are consistently associated with a subsequent lower risk of kidney failure. The sodium glucose co-transporter 2 inhibitor dapagliflozin significantly reduced albuminuria in patients with type 2 diabetes. Whether this effect persist in patients with chronic kidney disease (CKD) with and without diabetes is unknown. We therefore assessed and compared the effects of dapagliflozin on albuminuria in patients with CKD with and without type 2 diabetes from the DAPA-CKD trial. Method: We randomized 4304 patients with CKD and an eGFR of 25-75 ml/min/1.73m 2 and urinary albumin-to-creatinine ratio (UACR) 200-5000 mg/g to dapagliflozin (10 mg once daily) or placebo. Change in albuminuria was a pre-specified exploratory outcome. We used regression in UACR stage, defined as a transition from macroalbuminuria (≥300 mg/g) to micro- or normoalbuminuria (<300 mg/g), and progression in UACR stage, defined as a transition from non-nephrotic (<3000 mg/g) to nephrotic range albuminuria (≥3000 mg/g), as additional endpoints. Subgroup analyses were performed according to baseline type 2 diabetes status. Results: Median (25th to 75th Percentile) UACR was 949 (477-1885) mg/g. In patients with and without type 2 diabetes baseline median UACR was 1017 mg/g and 861 mg/g, respectively. Dapagliflozin, compared to placebo, reduced UACR by 29.3% (95% confidence interval [CI] 25.2, 33.1; p<0.001), with a 35.1% (95%CI 30.6, 39.4) reduction in patients with type 2 diabetes and 14.8% (95%CI 5.9, 22.9) reduction in patients without type 2 diabetes (p for interaction <0.001). Among 3860 patients with UACR ≥300 mg/g at baseline, dapagliflozin significantly increased the likelihood of regression in UACR stage (hazard ratio [HR] 1.81; 95%CI 1.60, 2.05). The corresponding HRs for patients with and without type 2 diabetes were 2.06 (95%CI 1.78, 2.39) and 1.33 (95%CI 1.07, 1.66), respectively (p for interaction 0.001). Among 3820 patients with UACR <3000 mg/g at baseline, dapagliflozin significantly decreased the risk of nephrotic range albuminuria (HR 0.41; 95%CI 0.32, 0.52). The corresponding HRs for patients with and without type 2 diabetes were 0.39 (95%CI 0.29, 0.51) and 0.50 (95%CI 0.30, 0.82), respectively (p for interaction 0.401). Conclusion: In patients with CKD with and without type 2 diabetes dapagliflozin significantly reduced albuminuria, with a larger reduction in patients with type 2 diabetes. The similar effects of dapagliflozin on clinical outcomes in patients with or without type 2 diabetes, but different effects on UACR suggest that part of dapagliflozin's protective effect in patients without diabetes is mediated through pathways unrelated to UACR reduction.